Identify and Diagnose the Causes of Financial Funding using the Root Cause Analysis Technique (Journal of Engineering, 2020)
The analysis of the root cause techniques is a reasonable option to be made to assess the root causes of the funding of construction projects. There are a variety of issues related to financing in construction industries in Iraq. The root,cause analysis is the impact of security and social conditions on financial funding. Variety tools of root cause analysis have originated from literature, as common methods for the detection of root causes. The purpose of this study was to identify and diagnose causes that lead to obstruction of financial funding in the construction projects in the republic of Iraq from the contractors' point of view and their interaction with a number of variables. The study diagnosed nine causes of financial funding in construction projects in Iraq. They are  Pareto,Diagram (PD), and the Five  Why, Analysis. It is found that the reasons (the organization's or the contracting company's reputation, the effect of expertise and skill of the organization or contracting company in obtaining finance & the impact of security and social conditions on the financial funding), came of degree important. In comparison, other reasons came of degree, average important.